NILAI-NILAI PENDIDIKAN AGAMA HINDU DALAM DONGENG I BELOG - Suadnyana, Ida Bagus Putu Eka (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
Balinese fairy tales contain many educational values related to Hindu religious education materials. This research was conducted to answer the question of whether the educational values of Hinduism contained in Balinese fairy tales are used as a medium for Hindu religious education at SD Negeri 11 Kesiman and how effective the use of Balinese fairy tales as a medium for Hindu religious education is in shaping children's attitudes and character. Based on this analysis, the research results obtained, The educational values in the Bali I Belog fairy tale are the educational values of virtue, courage, spirituality (spiritual intelligence), wisdom and happiness. The media used has a high effectiveness (right on target) in shaping the attitudes and character of children who have been taught to practice in everyday life.